Co-designing a co-design tool to strengthen ideation in digital experience design at museums. Issue 2 (3rd April 2022) - Olesen, Anne Rørbæk; Holdgaard, Nanna; Løvlie, Anders Sundnes
ABSTRACT: This article presents and discusses a paper-based co-design tool that was developed in order to strengthen ideation in digital experience design processes at museums. The tool, called the ASAP Map, was co-designed as part of an action research project with 10 museums from EU and the USA. The museum partners used the tool in their home institutions and the article focuses on their feedback and the following iterations of the tool through ongoing feedback loops. Concludingly, the usefulness and applicability of the tool is discussed, also touching on the relevance of this study for the broader co-design field.